+0  
 
0
27
1
avatar

What is the solution to (x + 2)(x - 3)^2 > 0?

 

 Sep 7, 2020
 #1
avatar+126 
+1

We can set it equal to zero. \((x+2)(x-3)^2=0\rightarrow x=-2,3\). Now we can try a value that is greater than 3 to eliminate the bottom choice. Lets do 4. Note that (4+2)(4-3)^2 is greater than 0, so it is not choice 3. Now to eliminate choice 1, we try a number less than -2, say -4. (-4+2)(-4-3)^2=(-2)49=-98, not greater than 0. So the answer is choice 2.

 Sep 7, 2020

53 Online Users

avatar
avatar
avatar